Improved performance of lead-tin mixed perovskite solar cells with PEDOT:PSS treated by hydroquinone. (1st May 2020) - Zhang, Meiying; Chi, Dan; Wang, Junfeng; Wu, Fengmin; Huang, Shihua
Highlights: Efficiency of PVSCs after HQ treatment increases from 13.85% to 14.65%. HQ modification lowers interface barrier between PEDOT:PSS and the active layer. Leakage current in PVSC with HQ-modified PEDOT:PSS is significantly reduced. Abstract: Low bandgap lead-tin (Pb-Sn) hybrid perovskite solar cells (PVSCs) have gained a great deal of attentions due to their wide optical absorption range and environmental friendliness. Poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) is widely used as a hole transport layer for PVSCs. However, the metallic property of PEDOT:PSS causes a barrier at the interface between it and the active layer, thereby hindering the transport of photogenerated carriers. In this paper, in order to eliminate the influence of the interfacial barrier, the PEDOT:PSS surface was treated by hydroquinone (HQ), which lowers the hole transport barrier at the interface, and consequently reduces the interfacial resistance as well. The leakage current in the device with the HQ-treated PEDOT:PSS is significantly reduced, and the surface modification improves the interfacial contact. Compared with the Pb-Sn hybrid PVSCs with the PEDOT:PSS hole transport layer, the power conversion efficiency of PVSCs with the HQ-PEDOT:PSS hole transport layer is improved by 5.7%.